Globally competent engineers: do international experiences matter? - Cook, Alistair, author (Colorado State University. Libraries, 2017)
Study abroad programs and international development organizations give engineering students opportunities to prepare themselves as global professionals through academic and/or hands on practical engineering experiences but does their impact on student development justify the cost? How do students taking part in these opportunities enculture and develop as global citizens compared with student that only undertake engineering design projects on campus. This study aims to compare student’s experiences and preparedness to work in global engineering through comparing and contrasting different models of on campus and international based, curricular and co-curricular design programs for their impact on students professional and global preparedness.
069 - Alistair Cook